2018
DOI: 10.1038/s41598-018-27592-x
|View full text |Cite
|
Sign up to set email alerts
|

Nesfatin-1 in the dorsal raphe nucleus influences visceral sensitivity via 5-HT neurons in male maternally separated rats

Abstract: Nesfatin-1, a satiety molecule processed from nucleobindin2 (NUCB2), is implicated in visceral hypersensitivity in rats and colocalized with 5-hydroxytryptamine (5-HT) in the dorsal raphe nucleus (DRN). Maternal separation (MS) in rats contributes to visceral hypersensitivity via elevated expression of 5-HT in the DRN. Intracerebroventricular injection of nesfatin-1 activates DRN 5-HT neurons. In this study, A model of visceral hypersensitivity was developed by subjecting rats to MS. Colorectal distension was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…In addition, sensitization and upregulation of microglial toll-like receptor 4 (TLR4) signaling activity in the PVN (Tang et al, 2017), ephrin-B2/EphB1 spinal signaling pathway (Theofanous et al, 2020), and nerve growth factor (NGF)-mediated tropomyosin receptor kinase A (TrkA) signaling (Wong et al, 2019) were involved in MS-induced visceral hypersensitivity. Moreover, various important signaling molecule dysfunctions were also involved in MS-induced visceral hypersensitivity, such as elevated expression of Nesfatin-1 in the dorsal raphe nucleus (DRN) (Zhang et al, 2018). Together, these studies focused the mechanism of MS-induced visceral hypersensitivity in adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, sensitization and upregulation of microglial toll-like receptor 4 (TLR4) signaling activity in the PVN (Tang et al, 2017), ephrin-B2/EphB1 spinal signaling pathway (Theofanous et al, 2020), and nerve growth factor (NGF)-mediated tropomyosin receptor kinase A (TrkA) signaling (Wong et al, 2019) were involved in MS-induced visceral hypersensitivity. Moreover, various important signaling molecule dysfunctions were also involved in MS-induced visceral hypersensitivity, such as elevated expression of Nesfatin-1 in the dorsal raphe nucleus (DRN) (Zhang et al, 2018). Together, these studies focused the mechanism of MS-induced visceral hypersensitivity in adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…This system can send fibers in a top-down manner to the dorsal spinal horn to inhibit pain transmission (Millan, 2002). The system comprises of the PAG, DR, rostral-ventromedial medulla (RVM), and LC (Reynolds, 1969;Francois et al, 2017;Torralba et al, 2018;Zhang et al, 2018). The system also sends dense connections to the CSF-contacting nucleus, which might be a novel pathway in pain modulation.…”
Section: Painmentioning
confidence: 99%
“…Some studies have suggested that central and peripheral nervous factors are involved in this process. For example, the activation of DRN 5-HT neurons might play a crucial role in visceral hypersensitivity [13], and impaired 5-HT reuptake by intestinal epithelial cells could lead to elevated levels of 5-HT in the colon, which could potentially influence the pathogenesis of IBS-D [14]. Therefore, how to restore the 5-HT equilibrium in the DRN (central) and intestine (peripheral) poses a challenge in the treatment of IBS-D.…”
Section: Introductionmentioning
confidence: 99%